Hubungan antara Homesickness terhadap Penyesuaian Diri pada Santri Tahun Pertama di Pondok Pesantren Modern Diniyyah Pasia - Irhamni, Shakira Ghaniya; Fikry, Zulian (Lembaga Yasin AlSys, 2025)
Pesantren are Islamic educational institutions that play a vital role in shaping the character and Islamic values of students (santri) through a disciplined communal lifestyle. For new santri, adapting to the pesantren environment often presents challenges, particularly due to homesickness arising from separation from family and familiar surroundings. This study aims to examine the relationship between homesickness and the adjustment process of new santri at Pondok Pesantren Modern Diniyyah Pasia. A quantitative correlational approach was employed, involving 192 new santri selected using a total sampling technique. The instruments used were the Homesickness Scale by Stroebe et al. (2002) and the Adjustment Scale by Schneiders (1960). Data analysis using Spearman’s correlation produced a rho (ρ) coefficient of 0.484 with a significance level of p = 0.001 (p < 0.05), indicating a significant positive relationship between homesickness and adjustment. This means that the higher the level of homesickness, the greater the challenge in the adjustment process for new santri. These findings contribute to a deeper understanding of the psychological dynamics experienced by new students and serve as a foundation for developing more effective adaptation support programs within the pesantren environment.